Design Of An E-Commerce Information System For Concert Ticket Sales Based On A Website - Anggraini, Putri Aprilia; Andriyani, Kirana; Tantowi, Idham (Jurnal Multidisiplin Sahombu, 2024)
The development of information technology, particularly the internet, has had a significant impact on various aspects of life, including business and commerce. One of the most noticeable effects is the increasing popularity of online transactions or e-commerce. E-commerce systems provide convenience for consumers to carry out transactions online without the limitations of place and time. In the entertainment industry, especially music concerts, online ticket sales through e-commerce systems offer practical solutions to address the issues arising from conventional methods. This research aims to design and develop a website-based e-commerce information system for concert ticket booking. The system is designed to provide users with convenience in booking concert tickets online, accessing the latest information about concert schedules and locations, and selecting flexible payment methods. The research methodology used is the waterfall approach, which consists of the stages of data collection, requirements analysis, system design, implementation, testing, and system maintenance. The results of this research show that the website-based e-commerce concert ticket system can improve transaction efficiency, expand market reach, and provide users with easier access. Additionally, the system is expected to enhance user satisfaction by providing fast, practical, and flexible services. It is hoped that the system will continue to evolve through feedback and suggestions from users to further improve functionality and user convenience in the future.